STUDENTS’ PERSPECTIVES OF YOUTUBE USAGE IN DEVELOPING AUTONOMOUS LEARNING IN ELT CONTEXTS - Astri Perdani, Mutiara; Rahayu, Nurita; Nurul Inayah, Suci; Azka, Alifa; Fatwa Mulyati, Yatni (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
YouTube is a well-known platform that everyone can use in every context, including the educational field. Despite the enormous benefit of YouTube usage in the learning context, only a little has been discussed about how YouTube can be used in developing students' autonomous skills. This current research aims to explore students' perceptions of the role of YouTube videos in developing students' autonomous learning and English language skills. This research was examined using a qualitative design and a type of data collection using a closed-ended questionnaire distributed to students in the form of a Google Form. The research subjects include 11 students of 5th-semester English education majors at State Islamic University Syarif Hidayatullah Jakarta who utilize YouTube to study English outside of class. Findings showed that YouTube is effective in developing autonomous learning skills. Furthermore, a major number of students specifically identified listening and vocabulary skills as areas where YouTube may help their autonomous learning activities.